Persepsi Guru Terkait Implementasi Kurikulum Merdeka di Sekolah Dasar Pada Mata Pelajaran IPAS - Nasa Mayyisi Ikhsani Ikhsani; Iqnatia Alfiansyah Alfiansyah (Jurnal Elementaria Edukasia, 2023)
Curriculum changes often occur in Indonesia, starting from Indonesia's independence until in 2022 through Mr. Nadiem Makarim, the Ministry of Education and Culture (Kemendikbud), a new curriculum education program was born, namely the Merdeka Curriculum by combining science and social studies as the two subjects into IPAS. This study aims to determine the views on the implementation of the independent curriculum by teachers in elementary schools in the IPAS subject. The method used in this research is Descriptive Qualitative with data collection through interview and observation techniques. Meanwhile, data analysis was carried out by data reduction, data presentation and conclusion drawing. This research focused on 4th grade elementary school teachers consisting of 3 Almadany Elementary School teachers in Gresik City. The results of this study indicate that teachers have a good perception of the independent curriculum in IPAS subjects, teachers are more active and creative in developing learning and learning media in the independent curriculum. Teachers are considered ready to carry out this IPAS learning activity, seen from the planning process and the results of interviews that have been conducted with the availability of fulfilling and adequate facilities at Almadany Elementary School, not only that this independent curriculum helps students to be more free to express their activities of interest. In IPAS learning, students are more focused on PJBL and PBL learning so that students can be more independent, critical and develop their curiosity and the use of Pancasila and P5 student profiles must also be applied in the applicable learning process. Curriculum changes often occur in Indonesia, starting from Indonesia's independence until in 2022 through Mr. Nadiem Makarim, the Ministry of Education and Culture (Kemendikbud), a new curriculum education program was born, namely the Merdeka Curriculum by combining science and social studies as the two subjects into IPAS. This study aims to determine the views on the implementation of the independent curriculum by teachers in elementary schools in the IPAS subject. The method used in this research is Descriptive Qualitative with data collection through interview and observation techniques. Meanwhile, data analysis was carried out by data reduction, data presentation and conclusion drawing. This research focused on 4th grade elementary school teachers consisting of 3 Almadany Elementary School teachers in Gresik City. The results of this study indicate that teachers have a good perception of the independent curriculum in IPAS subjects, teachers are more active and creative in developing learning and learning media in the independent curriculum. Teachers are considered ready to carry out this IPAS learning activity, seen from the planning process and the results of interviews that have been conducted with the availability of fulfilling and adequate facilities at Almadany Elementary School, not only that this independent curriculum helps students to be more free to express their activities of interest. In IPAS learning, students are more focused on PJBL and PBL learning so that students can be more independent, critical and develop their curiosity and the use of Pancasila and P5 student profiles must also be applied in the applicable learning process.